Testimonio : a documentary history of the Mexican American struggle for civil rights - Rosales, Francisco A. (Francisco Arturo) (Hispanic civil rights series., 2000)
Historical documents help chronicle the struggle of Mexican Americans for equal civil rights in the United States from the early 1800s through the modern era, with individual prefaces for each document and suggestions for further reading.